Men's more frequent predisposing factors in infectious endocarditis facilitate improvement of outcomes by shortening of diagnostic delay - Andreß, S.; Reischmann, K.; Markovic, S.; Rohlmann, F.; Hay, B.; Rottbauer, W.; Buckert, D.; d'Almeida, S. (Frontiers in Cardiovascular Medicine, 2025)
IntroductionDespite growing evidence for sex-specific differences in cardiovascular disease, sex is poorly considered in the management of infectious endocarditis (IE).PurposeThis study aimed to assess sex-specific aspects in diagnosing IE.MethodsAll consecutive patients admitted at Ulm University Heart Center with suspected IE between 2009 and 2019 were included. IE was diagnosed using the Duke criteria. Risk factors, clinical presentation and in-hospital outcomes along with the impact of diagnostic delay were compared between male and female patients.ResultsIE was diagnosed in 96 of 118 men (81.4%) and 33 of 45 women (73.3%) (p = 0.121). Time to diagnosis was similar between the groups (p = 0.598). Regarding patient characteristics, men were younger (65.5 vs. 74.3 years, p = 0.006). Men exhibited a higher prevalence of predisposing cardiac conditions (p = 0.012) due to a higher frequency of a history of implantable cardioverter defibrillator implantation (p = 0.004), and were more likely to have poor dental status (p = 0.001), and coronary artery disease (p = 0.002). The incidence of the complications of heart failure with reduced ejection fraction (p = 0.007) and new-onset dialysis (p = 0.012) were higher, the time in the intensive care unit (p = 0.012) longer. Male sex was the only independent risk factor for in-hospital mortality [p = 0.036, HR 4.127 (95%-CI 1.096-15.538)]. Notably, only in the male cohort, a shorter time to diagnosis was associated with a lower mortality rate (p = 0.035, optimal cut-point 3.5 days). Men diagnosed within 3.5 days had a mortality rate of 13.5% compared to 31.8% for those diagnosed later (p = 0.028).ConclusionMen with suspected IE are younger, have more predisposing factors and experience a more complicated course of disease, while benefiting from early diagnosis. Therefore, recognizing the heightened risk profile specific to men during diagnosis can help to address their poorer prognosis.